Affect as methodology: Feminism and the politics of emotion - Åhäll, Linda (International Political Sociology, 2018)
International relations scholars are increasingly paying attention to “the emotional” as a way to understand global politics. What is often missing from these conversations is feminist knowledge on affect, and also discussions about methodology. By presenting a feminist methodological approach to the affective-discursive to analyze the politics of emotion, this paper aims to fill this gap. It starts by discussing feminist critiques of the “affective turn.” Then, a methodological framework of gender, discourse, and affect as a structure that “goes-without-saying” is presented. Hemmings’ concept of affective dissonance is used as a tool guiding a feminist curiosity, useful to zoom in on the political puzzle of what emotion (in its broadest sense) does. The third section draws on two examples of being emotional about violent “Woman” to illustrate how moments of affective dissonance spark a feminist curiosity about gender, agency, and political violence. In conclusion, the paper argues that feminist knowledge on affect offers a way to re-tune, reset, and reimagine research on the politics of emotion. By prioritizing affect as methodology, feminist knowledge should be valuable for critical endeavors interested in changing the status quo, no matter if the political puzzle is about gender or not.
https://academic.oup.com/ips/article/12/1/36/4816223
Keywords: corps; discipline; genre; histoire et politique; méthodologie; relations internationales; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; thématiques; violences; émotions

Territoires de libération : perspectives féministes musulmanes - Benhadjoudja, Leïla (Tumultes, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; corps; cours; discipline; discours dominant; fem3400; féminisme islamique; féminisme musulman; histoire et politique; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques

Les solidarités familiales sous l’angle du travail: un siècle au Québec - Kempeneers, Marianne; Van Pevenage, Isabelle; Dandurand, Renée B. (Nouvelles Questions Féministes, 2018)
Les femmes sont le pivot des solidarités familiales, c’est un fait solidement documenté. Malgré cette évidence empirique, les solidarités familiales n’occupent qu’une place fort discrète dans l’univers théorique des rapports sociaux de sexe, contrairement par exemple au travail domestique ou, plus récemment, au travail du care. Les auteures s’interrogent ici sur cet état de fait. Elles proposent ensuite une lecture des solidarités familiales avec, pour ancrage, le paradigme fondateur que constitua la refonte du concept de travail par les courants féministes matérialistes. Adoptant une perspective historique et macrosociologique, cet article est l’occasion de prendre du recul face à un certain nombre de résultats issus d’une vaste enquête que les auteures avaient menée en 2004 sur les transformations des solidarités familiales au Québec au long du XXe siècle. La profondeur historique de cette enquête fait en sorte que ces données, bien que recueillies en 2004, restent pertinentes pour leur propos, à savoir jeter un éclairage sur les logiques reliant les évolutions concomitantes des solidarités familiales, du travail des femmes et des politiques publiques au Québec durant ce siècle crucial de son histoire.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; famille; histoire et politique; hétérosexualité; inégalités; maternité; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques; travail